2018
DOI: 10.15252/emmm.201809158
|View full text |Cite
|
Sign up to set email alerts
|

In vivo generation of human CD 19‐ CAR T cells results in B‐cell depletion and signs of cytokine release syndrome

Abstract: Chimeric antigen receptor (CAR) T cells brought substantial benefit to patients with B‐cell malignancies. Notwithstanding, CAR T‐cell manufacturing requires complex procedures impeding the broad supply chain. Here, we provide evidence that human CD19‐CAR T cells can be generated directly in vivo using the lentiviral vector CD8‐LV specifically targeting human CD8+ cells. Administration into mice xenografted with Raji lymphoma cells and human peripheral blood mononuclear cells led to CAR expression solely in CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 37 publications
(41 reference statements)
2
93
0
2
Order By: Relevance
“…A single systemic injection of CD19-CAR-encoding CD8-LVs into immune-deficient mice engrafted with a human blood system generated in vivo CAR T cells, which effectively wiped out the human B cells (Figure 1). 7 This outcome supports the feasibility of in vivo CAR T cell therapy. Remarkably, NiV-LVs could be produced at up to two orders of magnitude higher titers compared to their MV-based counterparts and were at Figure 1.…”
Section: Demonstrated Exclusive Transduction Of Cd4 + or Cd8 + T Cellsupporting
confidence: 57%
“…A single systemic injection of CD19-CAR-encoding CD8-LVs into immune-deficient mice engrafted with a human blood system generated in vivo CAR T cells, which effectively wiped out the human B cells (Figure 1). 7 This outcome supports the feasibility of in vivo CAR T cell therapy. Remarkably, NiV-LVs could be produced at up to two orders of magnitude higher titers compared to their MV-based counterparts and were at Figure 1.…”
Section: Demonstrated Exclusive Transduction Of Cd4 + or Cd8 + T Cellsupporting
confidence: 57%
“…Precise in vivo tracking of engineered cells using can also assist in this task by determining their biodistribution and homing to the tumor as well as evaluating their persistence [68,365]. Finally, one can hope that technological advances will simplify the manufacturing process of engineered T-cells and will even lead to the implementation of in vivo genetic engineering strategies [366]; preliminary exciting studies showed that DNA-carrying nanoparticle can selectively deliver CAR genes into host T cells facilitating tumor regression as conventional. These reprogrammed T cells remained functional as a 'living drug' and ultimately differentiated into long-lived memory T cells [367].…”
Section: Discussionmentioning
confidence: 99%
“…Smith and colleagues demonstrated that a CD3‐targeted anti‐CD19 CAR DNA‐containing nanoparticle was able to successfully reprogram T cells in vivo and redirect them against CD19‐positive targets . In a similar approach, Pfeifer and colleagues were able to successfully genetically engineer CD8+ T cells in vivo utilizing a CD8‐targeted lentivirus carrying a gene encoding an anti‐CD19 CAR, and demonstrated that these endogenously generated CAR T cells were capable of eliminating CD19 targets . Although these strategies will have major regulatory hurdles to overcome if they move toward the clinic, they represent a novel approach to cut production times and costs.…”
Section: Limitationsmentioning
confidence: 99%